Bioactive compounds content of chimarrão infusions related to the moisture of yerba maté (Ilex Paraguariensis) leaves - Bastos,Deborah H. M. (2006)
The aim of this study was to evaluate the effects of the processing stages of yerba maté (Ilex paraguariensis) on the moisture content of the leaves and the efficiency of the aqueous extraction of some bioactive substances. Samples of yerba maté were analyzed for caffeine, phenolic acids (caffeic acid, 5-caffeoilquinic acid) and flavonoids (quercetin, kaempferol and myricetin) by HPLC equipped with a diode array detector. Processing widely influenced the caffeine and 5-caffeoilquinic acid content of the aqueous extract (p < 0.05), which was related to the moisture content of the leaves. Caffeic acid was present in 45% of the in infusions from dried mate leaves. Quercetin, myricetin and kaempferol were not detected.